Analisis Sikap Multiatribut Fishbein Terhadap Pasar Sampangan Kota Semarang Pasca Relokasi Penjualan - Siti Ridloah; Vini Wiratno Putri; Nurjannah Rahayu Kistanti (Conference In Business, Accounting, And Management (CBAM), 2012)
The objective of the research is to identify consumer attitudes toward the attributes forming consumer perceptions and analyze the differences in consumer attitudes toward Sampangan Market before and after the relocation. Variabels of this study are divided into two groups: an evaluation of the attribute variabels into consideration consumers in choosing where to shop (variabel ei). The second variabel is the strength of the belief that the object being assessed has these attributes (variabel bi). The data analysis techniques used descriptive analysis and quantitative models multiatribut Fishbein attitude. Based on this research, consumer attitudes toward shopping attributes based on the evaluation of the importance of the attribute is strongly influenced by the price, speed of service, thelocation, the atmosphere and the physical condition of the shopping and completeness of product and promotion. Based on the evaluation of the level of confidence in the market Sampangan new attribute almost all the attributes believed was good except attribute consumer advertising and promotion. Based on the analysis calculations multiatribut Fishbein attitude is generally known that consumers preferred the new Sampangan Market compared to the old Sampangan market. The results of this study are expected to facilitate the formulation of plans, policies, regulations and implementation strategies specifically related to the development of traditional markets so that it can increase the economic empowerment that ultimately lead to a multiplier effect for the welfare of the societies.Keywords: Consumer Attitude, Attitude Multiatribut Fishbein Model.